Writing, Medium, Machine: Modern Technographies - Trotter, David; Pryor, Sean (Technographies, 2016)
Writing, Medium, Machine: Modern Technographies is a collection of thirteen essays by leading scholars which explores the mutual determination of forms of writing and forms of technology in modern literature. The essays unfold from a variety of historical and theoretical perspectives the proposition that literature is not less but more mechanical than other forms of writing: a transfigurative ideal machine. The collection breaks new ground archaeologically, unearthing representations in literature and film of a whole range of decisive technologies from the stereopticon through census-and slot-machines to the stock ticker, and from the Telex to the manipulation of genetic code and the screens which increasingly mediate our access to the world and to each other. It also contributes significantly to critical and cultural theory by investigating key concepts which articulate the relation between writing and technology: number, measure, encoding, encryption, the archive, the interface. Technography is not just a modern matter, a feature of texts that happen to arise in a world full of machinery and pay attention to that machinery in various ways. But the mediation of other machines has beyond doubt assisted literature to imagine and start to become the ideal machine it is always aspiring to be. Contributors: Ruth Abbott, John Attridge, Kasia Boddy, Mark Byron, Beci Carver, Steven Connor, Esther Leslie, Robbie Moore, Julian Murphet, James Purdon, Sean Pryor, Paul Sheehan, Kristen Treen.